Financial Performance Analysis of The National Zakat Management Institution Rumah Amal Salman - Aditama, Rila; Yulianti, Lina; Muslih, Rd. Amar (Filantropi : Jurnal Manajemen Zakat dan Wakaf, 2025)
This study aims to evaluate the financial performance of the National Zakat Management Institution Rumah Amal Salman during the 2021–2023 period using the financial ratio analysis approach established by the PUSKAS BAZNAS guidelines. The research applies a descriptive qualita tive method supported by quantitative data obtained from the institution’s audited annual financial statements. Data were collected through documentation, observation, and literature review, then analyzed using four main ratio categories: activity, efficiency, amil funds, and growth. The data analysis process includes classifying financial accounts, compiling them into analytical tables, calculating financial ratios, and interpreting the results according to OPZ performance standards. The findings indicate that Rumah Amal Salman was categorized as effective in distributing Zakat, Infaq, and Sadaqah (ZIS) funds and relatively efficient in collection activities. However, operational cost efficiency still requires improvement. The amil fund ratio remains within acceptable limits, while the growth ratio shows a positive trend although it has not yet reached an optimal level. These results highlight the institution’s good financial governance and provide insights for enhancing transparency, accountability, and public trust in zakat management organizations.